2017
DOI: 10.1037/xge0000326
|View full text |Cite
|
Sign up to set email alerts
|

A quantum probability framework for human probabilistic inference.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThere is considerable variety in human inference (e.g., a doctor inferring the presence of a disease, a juror inferring the guilt of a defendant, or someone inferring future weight loss based on diet and exercise). As such, people display a wide range of behaviors when making inference judgments.Sometimes, people's judgments appear Bayesian (i.e., normative),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 87 publications
4
36
0
Order By: Relevance
“…Yet participants judged that pfalse(yi1false|yj0false)<pfalse(yi1false|yj1false) instead. This apparent expectation that the causes of a common effect graph are positively correlated has been observed in other studies (Luhmann & Ahn, 2007; Perales, Catena, & Maldonado, 2004; Rehder, 2014, 2015, 2018; Rehder & Burnett, 2005; Rottman & Hastie, 2016; Trueblood, Yearsley, & Pothos, 2017; cf. Von Sydow, Hagmayer, Meder, & Waldman, 2010).…”
Section: Empirical Testssupporting
confidence: 79%
See 4 more Smart Citations
“…Yet participants judged that pfalse(yi1false|yj0false)<pfalse(yi1false|yj1false) instead. This apparent expectation that the causes of a common effect graph are positively correlated has been observed in other studies (Luhmann & Ahn, 2007; Perales, Catena, & Maldonado, 2004; Rehder, 2014, 2015, 2018; Rehder & Burnett, 2005; Rottman & Hastie, 2016; Trueblood, Yearsley, & Pothos, 2017; cf. Von Sydow, Hagmayer, Meder, & Waldman, 2010).…”
Section: Empirical Testssupporting
confidence: 79%
“…Trueblood et al (2017) also found differences in the magnitude of Markov violations and, moreover, that those violations correlated with other measures, such as the magnitude of order effects (i.e., the difference between p ( Z | XthenY ) and p ( Z | YthenX )) and measures they referred to as reciprocity and memorylessness . These measures in turn correlated with subjects' performance on the cognitive reflection test (CRT), which is purported to measure differences in reasoners' tendency to emit intuitive versus deliberative responses (Frederick, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations